Pengaruh Hutang Luar Negeri dan Tingkat Suku Bunga Terhadap Pertumbuhan Ekonomi di Indonesia - Ramadian Syah.S (Universitas Batanghari Jambi, 2019)
The purpose of this research is to find out and analyse the national foreign debt, interest rates and economic growth in Indonesia and the 1998-2017 period to analyze the influence of national foreign debt, rates the applicable interest rate and economic growth in Indonesia on Period 1998-2017.This research is a desciptive quantitative research and analysis tool used in this research are simple linear regression is useful to see the direction of the relationship between the variable bound against free. For the purpose of answering the purpose number 2 used statistical test F test t. The correlation coefficient to know how the relationship between variables and coefficients of determination of useful to see the magnitude of the influence of the variable bound against free.Indonesia lies between 6 ° 08 ' North latitude and 11 ° 15 ' South latitude and between 94 ° 45 '-141 ° 05 ' East longitude and is traversed by the line of the Equator or the Equator located at latitude 0 °. Based on its geographical location, the archipelago of Indonesia located between Asia and Australia, as well as in the Continent between the Indian Ocean and the Pacific Ocean.The calculation SPSS Y = -2,869 + 1,738 X1 + 1,558 X2 + e of the equations looks positive influence between the national foreign debt (X1) and interest rates (X2) on growth in Indonesia (Y). From the result of the obtained values SPSS (coefficient) r2 this figure amounted 0,351 states that the variable national foreign debt (X1) and interest rates (X2) is able to explain the variabel growth in Indonesia (Y) is 13,2% and the remaining 64,9% is explained by other factors which is not included in the research model.The conclusions of this research are foreign debt and interest rates take effect simultaneously against economic growth. This is evidenced by the value F count greater than the value of F table (4.589 > 3.59) and significantly less than the value of the alpha (0.025 < 0.05) and foreign debt effect on economic growth. This is evidenced by the value t calculate t value is greater than the table (2.989 > 2.109) and significantly less than the alpha (0.008 < 0.05). Interest rates have an effect on economic growth. evidenced by the value t table (2.979 < 2.109) and significantly greater than the value of the alpha (0.008 > 0.05).